2020
DOI: 10.1098/rsos.190669
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the interplay of positive and negative selection forces that shaped mitochondrial genomes of Gammarus pisinnus and Gammarus lacustris

Abstract: We hypothesized that the mitogenome of Gammarus lacustris (GL), native to the Qinghai-Tibet Plateau, might exhibit genetic adaptations to the extreme environmental conditions associated with high altitudes (greater than 3000 m). To test this, we also sequenced the mitogenome of Gammarus pisinnus (GP), whose native range is close to the Tibetan plateau, but at a much lower altitude (200–1500 m). The two mitogenomes exhibited conserved mitochondrial architecture, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 78 publications
(134 reference statements)
0
14
0
Order By: Relevance
“…Despite the prevalence of purifying selection in mitogenomes, the possibility for positive selection acting on single codon positions cannot be excluded, and, potentially, can facilitate physiological adaptations to new environments [ 24 , 43 ]. In this study, the codon-based analyses of selection showed that several sites may be under positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prevalence of purifying selection in mitogenomes, the possibility for positive selection acting on single codon positions cannot be excluded, and, potentially, can facilitate physiological adaptations to new environments [ 24 , 43 ]. In this study, the codon-based analyses of selection showed that several sites may be under positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…Selection analyses show that negative (purifying) selection generally dominates mitochondrial genome evolution due to its importance in cellular respiration [ 71 , 81 , 82 ]. However, positive selection signatures can be detected in certain codons of mitochondrial Hyalella protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…have been sequenced recently from the representatives of both Baikalian species and several species of gen. Gammarus (Krebes and Bastrop, 2012;Romanova et al, 2016;Macher et al, 2017;Cormier et al, 2018;Sun et al, 2020). Since the proteins coded in mitochondrial DNA are not directly involved in morphogenesis, the deviations in the rate of their molecular evolution may serve as an indication of changes in the average rate of molecular evolution in the respective species.…”
Section: Several Mitochondrial Genomes (Mitogenomes)mentioning
confidence: 99%